Asia's Strategic Participation in the Group of 20 for Global Economic Governance Reform: From the Perspective of International Trade - Taeho Bark; Moonsung Kang (Asian Development Bank (ADB), 2011)
After considering the background to the G20 summit meetings after the recent global economic and financial crisis, this paper aims to identify the trade agenda that represents Asia's concerns for the global and regional trading system. Asia, in particular East Asia, has played an important role in evolving the global production and trade networks. The regional production network in East Asia became the major transmission mechanism of the crisis, resulting in a trade collapse, but Asia experienced a relatively quick rebound, demonstrating that its network was not derailed. Asian economies have also shifted their policy focus from multilateralism to regionalism, even though there are several challenges such as underuse and a shallowness of their regional trade agreements. This paper recommends that the Seoul Summit seek tangible results on resolving the stalemate of the Doha Development Agenda to strengthen the credibility of G20, integrate individual free trade agreements into broader regional trade agreements, and link the development agenda to trade.
hdl:11540/2055
Keywords: F13; F15; 330; global governance and Group of Twenty (G20); international and regional trade; global and regional production networks; global and regional trade systems